KEY ELEMENTS FOR SUCCESSFUL MOODLE 1.9 ADOPTION IN ONLINE LEARNING ENVIRONMENTS - Lim, Aaron Michael; Okonkwo, Chinyere Judith (Ayden Journal of Management and Social Sciences, 2024)
E-learning is a rapidly growing approach in higher education, driven by the need for innovation and competition among institutions. This method leverages information and communication technology tools to enhance individual and group learning experiences. As the landscape of education evolves, higher institutions are increasingly adopting e-learning to stay competitive, deliver content efficiently, and create global learning communities. E-learning eliminates the constraints of time and distance, providing students with access to a wide range of learning materials and the ability to pursue their education regardless of geographic location. However, while e-learning offers many advantages, its implementation is not without challenges. This paper explores the benefits and drawbacks of e-learning in higher education. It sheds light on how e-learning can help institutions gain a competitive edge while also addressing the limitations and issues that may arise during its implementation